2016
DOI: 10.1016/j.biomaterials.2015.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Successful endothelialization and remodeling of a cell-free small-diameter arterial graft in a large animal model

Abstract: The large number of coronary artery bypass procedures necessitates development of off-the-shelf vascular grafts that do not require cell or tissue harvest from patients. However, immediate thrombus formation after implantation due to the absence of a healthy endothelium is very likely. Here we present the successful development of an Acellular Tissue Engineered Vessel (A-TEV) based on small intestinal submucosa that was functionalized sequentially with heparin and VEGF. A-TEVs were implanted into the carotid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 137 publications
(138 citation statements)
references
References 53 publications
4
132
0
2
Order By: Relevance
“…Furthermore, the initial rate of compaction was ∼2.38% per hour for WT cells but less than half of that at ∼1.01% per hour for Cdh11 −/− cells. We also measured the mechanical properties and collagen content of tissue constructs prepared from Cdh11 −/− or WT mouse dermal fibroblasts, as we described in previous publications (DiazChavez et al, 2008;Liang et al, 2013;Koobatian et al, 2016). To this end, we prepared cylindrical tissue equivalents by embedding cells in fibrin hydrogels that were polymerized around cylindrical mandrels and cultured in the presence of TGF-β1 for 2 weeks.…”
Section: Cdh11mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the initial rate of compaction was ∼2.38% per hour for WT cells but less than half of that at ∼1.01% per hour for Cdh11 −/− cells. We also measured the mechanical properties and collagen content of tissue constructs prepared from Cdh11 −/− or WT mouse dermal fibroblasts, as we described in previous publications (DiazChavez et al, 2008;Liang et al, 2013;Koobatian et al, 2016). To this end, we prepared cylindrical tissue equivalents by embedding cells in fibrin hydrogels that were polymerized around cylindrical mandrels and cultured in the presence of TGF-β1 for 2 weeks.…”
Section: Cdh11mentioning
confidence: 99%
“…A ninhydrin assay was used for evaluation of elastin content and a hydroxylproline assay was used for the quantification of collagen as described previously (Koobatian et al, 2016). Briefly, tissues used for quantification of elastin and collagen were lyophilized to obtain the dry weight, which served as a normalization factor.…”
Section: Colorimetric Quantification Of Collagen and Elastin In Tissuesmentioning
confidence: 99%
“…In a recent study from our lab, heparin was employed to coat SIS by means of EDC-NHS chemistry, followed by immobilization of VEGF via binding to the heparin binding domain. These grafts exhibited high patency rates in the high flow environment of ovine carotid arteries and produced fully endothelialized, functional arteries as soon as one month post-implantation 50 . Unlike antibodies which have also been applied to capture EPCs from the host bloodstream 51,52 , VEGF enhances the survival, proliferation and cell spreading of captured progenitors 5356 , making it a more attractive option for functionalizing TEBVs.…”
Section: Recent Breakthroughs In Tissue Engineeringmentioning
confidence: 98%
“…Another study used a biodegradable elastomer that was replaced by a neoartery in a rat animal model 59 . ECs have been replaced by growth factors and antibodies which are capable of capturing host circulating EPCs 50 . Zhou et al have utilized heparin and VEGF to replace the endothelial lining, and have shown successful implantation in a canine arterial model 60 .…”
Section: Recent Breakthroughs In Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation